Enhancing English Language Teaching: Opportunities and Practices for Professional Growth (Siddhajyoti Interdisciplinary Journal, 2026)
This research paper aims at exploring the professional development opportunities and practices for the English language teachers using a qualitative approach in nature. Grounded in an interpretivist paradigm, the study utilizes narrative inquiry as its methodology to interpret data generated through online massaging responses. For the data generation, four secondary level English teachers from two different community schools in Sindhuli district were selecting using a purposive sampling procedure. Online semi-structured interviews via online messaging text platform were used for data collection. The study found that various opportunities and practices exist for the professional development of English language teachers in English Language Teaching (ELT) such as leadership training, management training, teacher professional development (TPD) training, workshops, seminars, refreshing training, teacher facilitator training, action research training, stream education training, support group training, customized training, action research, collaborative learning, and curriculum enlightenment training. Those teachers who involved reflective practices, they marked improvement in the classroom delivery and these practices translated into better students' outcomes. However, despite the available opportunities, several challenges were identified. The teachers often faced institutional barriers such as time limitations, insufficient funding, growing demand for quality education, unsupported administration. Additionally, geographical barriers, technological gaps impacted their ability to access online resources, implementing digital teaching methods and updated with modern educational tools.